Cardiovascular nurses' adherence to practice standards in in‐hospital telemetry monitoring. Issue 1 (10th April 2019) - Fålun, Nina; Oterhals, Kjersti; Pettersen, Trond; Brørs, Gunhild; Olsen, Siv S.; Norekvål, Tone M.; ,
Abstract: Background: Correct electrode placement and proper skin preparation for cardiac telemetry monitoring of patients at risk for arrhythmias increase the quality of the arrhythmic surveillance. Inconsistent arrhythmia surveillance can compromise patient safety and care outcomes. An inspection of international literature demonstrates that nurses generally do not adhere to cardiac monitoring standards. Aim: The aims of this study were to determine cardiovascular nurses' knowledge of and adherence to practice standards for cardiac surveillance and whether their knowledge and practice improves over time. Study design: A comparative study design was applied, and data were obtained by survey methodology. Methods: Nurse delegates at the Annual National Congress on Cardiovascular Nursing in Norway completed surveys in 2011 and 2017 (delegates from 44 and 38 hospitals, respectively). Results: In total, 363 cardiac nurses (70%) responded to the questionnaires. Of these, 95% were female, with a mean age of 41 years. In 2011, 97% of participants were unaware of international practice standards. However, by 2017 unawareness decreased to 78% ( P < .001). Despite their lack of knowledge of practice standards, 94% of participants often or always prepared patients' skin for telemetry; this improved from 2011 to 2017 ( P = .001). Overall, 73% of nurses never or seldom scrubbed or washed the patients' skin before electrode placement, and 38% of the electrodes were misplaced. In 2011, 49% of nurses used protective telemetry covers; this increased to 80% in 2017 ( P < .001). Overall, 64% always informed patients of the purpose of cardiac monitoring. Conclusion: A significant percentage of nurses fail to adhere to recommendations for electrode placement, skin preparation and providing patients with telemetry information. In order to raise the quality of arrhythmic surveillance, investment in educational programmes in cardiac telemetry monitoring is required. Relevance to Clinical Practice: Improved in‐hospital telemetry practice is required to ensure patient safety and better care outcomes.